Presidents, Prime Ministers and Chancellors Executive Leadership in Western Democracies - Helms, L.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2005)
How have the American presidency, the British premiership and the German chancellorship changed over the last half-century? Has there been convergence or divergence in the development of political leadership in the United States and in the two largest democracies of Western Europe? And what difference can individual leaders make in an ever-more complex political environment? Presidents, Prime Ministers and Chancellors addresses these questions by looking at the leadership performance of more than two dozen American presidents, British prime ministers and German chancellors of the post-1945 period. In so doing, it offers a unique perspective on the nature of executive leadership in Western democracies that takes into account both the international and the historical dimension of comparison.
Keywords: Comparative politics; Political science; Comparative Politics; Political Science